2021
DOI: 10.1002/jdd.12820
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of remote simulation‐based learning for periodontal instrumentation: A non‐inferiority study

Abstract: Objectives While numerous virtual/remote simulation‐based learning (SBL) modules were implemented due to the COVID‐19 pandemic, limited data on their effectiveness are available. This study aimed to investigate the effectiveness of a remote SBL module for periodontal instrumentation compared to traditional onsite SBL modules. Methods Calibrated faculty members have instructed in all modules. Synchronous remote SBL activities using a secure videoconferencing application, which replaced onsite practices, were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Positive findings for the effectiveness of DL have been reported in various areas of education with respect to student learning outcomes 16 . However, it is still uncertain if those findings generally apply to dental education since few systematic studies have investigated the impact of DL on dental education by means of student learning outcomes such as test scores 2,3 . One study used test scores as outcome variables, but test questions for their DL and CL groups were different.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Positive findings for the effectiveness of DL have been reported in various areas of education with respect to student learning outcomes 16 . However, it is still uncertain if those findings generally apply to dental education since few systematic studies have investigated the impact of DL on dental education by means of student learning outcomes such as test scores 2,3 . One study used test scores as outcome variables, but test questions for their DL and CL groups were different.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, preclinical periodontal education is composed of didactic and practical portions 1 . While simulation‐based learning is implemented to develop manual skills in the practical portion, 2 lectures, and summative assessments in the didactic portion comprise the majority of the entire preclinical periodontal courses. Traditional classroom learning (CL) had been employed in the second‐year periodontics course.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a high prevalence of dental students using online resources such as YouTube and Google searches to supplement their education 2 . Studies in dental schools have even found that using educational videos yielded high scores on clinical‐based exams 3 . Medical and dental students reported feeling that they are readily equipped to shift toward online education and that online study materials allow for flexibility with learning and improve understanding of content 4 …”
Section: Introductionmentioning
confidence: 99%
“…2 Studies in dental schools have even found that using educational videos yielded high scores on clinical-based exams. 3 Medical and dental students reported feeling that they are readily equipped to shift toward online education and that online study materials allow for flexibility with learning and improve understanding of content. 4 With increasing online educational resources becoming available, it is vital to ensure their quality, accuracy, and level of evidence as dental students learn from them to use in a clinical setting on live patients.…”
Section: Introductionmentioning
confidence: 99%